Elucidating the role of oxygen coverage in CO2 reduction on Mo2C. Issue 23 (18th October 2017) - Dixit, Mudit; Peng, Xi; Porosoff, Marc D.; Willauer, Heather D.; Mpourmpakis, Giannis
Abstract : Revealed linear relationships between oxygen coverage and electronic modification of the Mo2 C catalyst that tunes the reactivity for CO2 reduction. Abstract : Molybdenum carbide (Mo2 C) is a promising and low-cost catalyst for the conversion of CO2 to CO. However, the underpinning mechanism occurring on the catalyst surface and the understanding of the catalyst structure under the reaction conditions is still elusive. In this study, we employ first principles calculations to understand the CO2 dissociation mechanism on β-Mo2 C (001) under different oxygen coverage on the catalyst surface (oxycarbide). Our results demonstrate that with increasing oxygen coverage, there is an electronic modification on the catalyst surface ( e.g. d-band shift on Mo atoms), that in turn, tunes the interactions of the adsorbates and the CO2 dissociation barriers. Interestingly, we reveal linear relationships between the oxygen coverage and electronic modification with the reactivity of the catalyst. We show that CO2 can adsorb and dissociate on the oxygen covered Mo2 C surface, even in the presence of surface oxygen up to 0.5 monolayer (ML). Our results rationalize a series of experimental observations.